Big cleaning day: Pendidikan karakter dan pengabdian sosial di Masjid Ban Khlong Raet, Thailand - Meis Syifa Reillita; Abdul Rohim; Evy Fitria (Nur Science Institute, 2026)
This community service activity was motivated by the importance of implementing character education not only through theoretical learning in the classroom but also through direct, real-life activities involving students. This study aimed to implement character education through the Big Cleaning Day program as a form of social service at Ban Khlong Raet Mosque, Krabi, Thailand. The method used was a participatory approach involving students, teachers, and mosque administrators in all stages of the activity, including preparation, implementation, and evaluation. The results showed improvements in students’ cooperation, discipline, responsibility, and environmental awareness. In addition, the activity contributed positively to improving the cleanliness and comfort of the mosque environment. Based on the evaluation results, the participatory approach was found to be effective in internalizing character values through direct experience. Therefore, the Big Cleaning Day program can serve as an applicable and sustainable model of character education-based community service activities.